Development and Clinical Validation of a Potential Penside Colorimetric Loop-Mediated Isothermal Amplification Assay of Porcine Circovirus Type 3 - Zhang, Jie; Li, Miaomiao; Ou, Yunwen; Chen, Danian; Ding, Yaozhong; Zhang, Weibing; Li, Yanjun; Hou, Qian; Li, Xiaoyun; Zhou, Luoyi; Podgorska, Katarzyna; Zaberezhny, Alexei D.; et al. (Frontiers in Microbiology, 2022)
Porcine circovirus type 3 (PCV3), a novel circovirus, imposes great burdens on the global pig industry. The penside tests for detecting PCV3 are critical for assessing the epidemiological status and working out disease prevention and control programs due to the unavailability of a commercial vaccine. A one-step molecular assay based on visual loop-mediated isothermal amplification (vLAMP) was developed for simple and rapid detection of PCV3. We compared its sensitivity and specificity with TaqMan quantitative real-time polymerase chain reaction (qPCR) and applied the developed assay in the epidemiological study of (n = 407) pooled swine sera collected from almost the entire mainland China during the years 2017–2018. We also explored the feasibility of the vLAMP assay for detecting raw samples without a prior DNA isolation step to expand its application capability. Results showed that the vLAMP assay could reliably detect the PCV3 cap gene with a detection limit of 10 DNA copies equal to that of the Taqman qPCR assay. In the epidemiological study, the PCV3 positive detection rate for 407 swine pooled sera detected by the vLAMP assay was 37.35% (152/407), whereas it was 39.01% (159/407) for Taqman qPCR. For the detection method without genome extraction, the results kept satisfactory specificity (100%) but displayed lower sensitivity (100% for CT < 32), indicating the direct detection is not sensitive enough to discriminate the samples with low viral loads. The one-step vLAMP is a convenient, rapid, and cost-effective diagnostic for penside detection and will enable the epidemiological surveillance of PCV3, which has widely spread in mainland China.